KEMAMPUAN SISWA DALAM MEMAHAMI PEMBELAJARAN BERBASIS PROJEK DI SEKOLAH DASAR - Tania Siringoringo; Ervinna Sigiro (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine the integration of Project Based Learning (PjBL) and Pancasila Learning in improving elementary school students' critical thinking skills. The method used is a literature review by collecting and analyzing information from various trusted sources. Through this literature review, researchers can clearly convey and explain to readers why the chosen research topic is a problem that needs to be researched. This covers both aspects of the subject to be researched and its context, and explains the relationship of this research to relevant previous research. The results of the study show that PjBL and Pancasila Learning have the potential to improve students' critical thinking skills through project-centered, collaborative and meaningful learning. The integration of PjBL and Pancasila Learning can be an effective strategy for improving elementary school students' critical thinking skills. Teachers need to have adequate training and support to implement this approach effectively.